BINAHONG LEAVES (ANREDERA CORDIFOLIA TENORE STEEN) EXTRACT AS AN ALTERNATIVE TREATMENT FOR PERINEAL WOUND HEALING OF POSTPARTUM MOTHERS - Dita Selvia Aditia; Syarief Thaufik Hidayat; Nur Khafidhoh; Suhartono Suhartono; Ari Suwondo (Belitung Raya Foundation, Indonesia, 2017)
Background: Perineal wounds are at risk for infection, without a good treatment, perineal wound can harbor sepsis and become a chronic, long-term problem. Binahong leaves is considered as an alternative to accelerate perineal wound healing process. Objective: To determine the effect of Binahong leaf extract (anredera cordifolia (tenore) steen) on perineal wound healing process in postpartum mothers. Methods: This study employed a quasi-experimental study with control group posttest-only design. The study was conducted in the working area of Telogosari Wetan Health Center and Health Center of Kulon Kota Semarang Indonesia in January-February 2017. There were 36 respondents selected using purposive sampling assigned in the intervention group (Binahong leaves extract) and the control group (Povidone Iodine 10%). REEDA scale was used for assessing perineal healing. Data were analyzed using Mann Whitney, Chi Square and Kruskal Wallis test. Results: Findings showed that the average day of perineal wound healing process in the Binahong leaves group was 6.11 days and in the povidone iodine group was 7.66 days. There was a statistically significant difference in the duration of wound healing between the experiment and control group with p-value 0,001 (p value <0.05). Conclusion: Binahong leaves extract is effective in healing perineal wound in postpartum mothers. Therefore, Binahong leaves are recommended to use as an alternative treatment for the mothers.